ANALISIS PERBANDINGAN SIFAT FISIS DAN MEKANIS PADA PISTON MOTOR PRODUK CHINA (KANZEN) DAN MOTOR PRODUK JEPANG (HONDA GL) - Sukahar; Hafid, Achmad; Suparja (JURNAL MEKANIKASISTA, 2024)
This research is about comparing the physical and mechanical properties of motorbike piston made in China (Kanzen) and motorbike pistons made in Japan (Honda GL). The aim is to find out which material structure is better between motorbike piston made in China and motorbike piston made in Japan. Because in field use Japanese motorbike pistons are superior to motorbike piston made in China.The piston is an engine component that changes or transfer combustion pressure into straight motion (sliding) which then, through the piston rod, piston rod and crankshaft, converts the straight motion of the piston into rotary motion. This piston has an aluminum alloy composition with the dominant elements, namely Mn, Zn, Ti, Cr, Pb, and Sn.From the test of the material composition of these two pistons, the material elements are almost the same, but the Honda GL motorbike pistons is better than the Kanzen motorbike pistons, judging from its elements. From the hardness test, it turns out that motorbike pistons made in China (Kanzen) are superior to pistons made in Japan (Honda GL) but that doesn’t mean that hard is good for the piston, then from the micro structure the piston of Japanese motorbikes (Honda GL) are better than Chinese motorbikes (Kanzen) because the crystals spread out so that they can cause cracks in the piston more quickly.